2017
DOI: 10.1016/j.osnem.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Multi-class machine classification of suicide-related communication on Twitter

Abstract: The World Wide Web, and online social networks in particular, have increased connectivity between people such that information can spread to millions of people in a matter of minutes. This form of online collective contagion has provided many benefits to society, such as providing reassurance and emergency management in the immediate aftermath of natural disasters. However, it also poses a potential risk to vulnerable Web users who receive this information and could subsequently come to harm. One example of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 50 publications
0
58
0
1
Order By: Relevance
“…ML applied to twitter found that Tweets could be a useful supplementary influenza surveillance tool and correlate well with official statistics . ML models have also been developed to classify suicide‐related communication on twitter . Natural language processing ML models have been applied to emergency medicine clinical documentation to detect influenza .…”
Section: Population and Social Media Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…ML applied to twitter found that Tweets could be a useful supplementary influenza surveillance tool and correlate well with official statistics . ML models have also been developed to classify suicide‐related communication on twitter . Natural language processing ML models have been applied to emergency medicine clinical documentation to detect influenza .…”
Section: Population and Social Media Analysismentioning
confidence: 99%
“…41,42 ML models have also been developed to classify suicide-related communication on twitter. 43 Natural language processing ML models have been applied to emergency medicine clinical documentation to detect influenza. 44 ML may also assist with the detection of novel BOX 1.…”
Section: Clinical Monitoringmentioning
confidence: 99%
“…posting frequency [ 5 , 19 ]) on social media platforms. Some recent efforts attempted to classify tweets by levels of distress [ 6 ], concerns [ 20 , 21 ] or types of suicidal communication [ 22 ] using machine learning or rule based approaches. However, few studies have been done mining the risk factors from social media.…”
Section: Introductionmentioning
confidence: 99%
“…Actually gaining access to names of all these deceased people would either rely on highly sensitive data disclosure by the authorities responsible for mortality statistics or the cooperation of all coroners in the country, which is unrealistic. A prospective study was important, as this data collection was linked to other studies of the use of social media in connection with suicide (see Burnap, Colombo, Amery, Hodorog & Scourfield, 2017;Scourfield et al, 2018).…”
Section: Methodsmentioning
confidence: 99%